2005
DOI: 10.1111/j.1600-0501.2005.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional composites manufactured with human mesenchymal cambial layer precursor cells as an alternative for sinus floor augmentation: an in vitro study

Abstract: Bone tissue engineering is a promising approach for treatment of defective and lost bone in the maxillofacial region. Creating functional tissue for load bearing bone reconstruction using biocompatible and biodegradable scaffolds seeded with living cells is of crucial importance. The aim of our study was to compare the effects of poly-lactic-co-glycolic acid (PLGA) and hydroxyapatite (HA) ceramic granulae on growth, differentiation, mineralization and gene expression of mandibular mesenchymal cambial layer pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…The effectiveness of scaffolds made from bioabsorbable materials such as PLLA in bone regeneration has been reported 9) . There are reports that osteogenic ability could be enhanced by improvements in the microstructure of such scaffold 10,11) .…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of scaffolds made from bioabsorbable materials such as PLLA in bone regeneration has been reported 9) . There are reports that osteogenic ability could be enhanced by improvements in the microstructure of such scaffold 10,11) .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies are currently focused on the development of 3D structures that mimic the anatomical and biochemical organization of cells and native matrix in order to achieve suitable mechanical properties for bone tissue [22] . Numerous materials have been shown to support in vitro bone formation by human cells, including bioceramics like HA, β-TCP, bio-glasses and biodegradable polymers [23,24] , and natural or synthetic collagen, fibrin, chitosan or polyesters [25,26] . Scaffolds containing composites of these materials provide an optimized and convenient alternative as they combine the advantages of both bioactive ceramics and biodegradable polymers [27][28][29][30][31] .…”
Section: Scaffoldsmentioning
confidence: 99%
“…Proofin-principle for bone tissue engineering using BMSC has been demonstrated in various animal models (for review see Cancedda et al, 2003); in addition, 7 human clinical studies had been conducted by 2010 (Chatterjea et al, 2010). However, several studies have also shown ASC and AO to be appropriate cell sources for bone regeneration (Zuk et al, 2001;Cowan et al, 2004;Hattori et al, 2006;Fröhlich et al, 2010;Turhani et al, 2005;Maličev et al, 2008).…”
Section: Treatment Of Bone Defectsmentioning
confidence: 99%